The Effect of Rewards, Communication and Teamwork on Employee Performance : JEL Classification: M12, M54, J24, D23, L93 - Irsyad Eka Putra Syam; Mujahid Yunus; Nurmadhani Fitri Suyuthi (Journal La Bisecoman, 2026)
This study aims to examine the effect of rewards, communication, and teamwork on employee performance at the Makassar Region V Airport Authority Office. A quantitative explanatory approach was employed to test the relationship between the independent variables, namely rewards, communication, and teamwork, and the dependent variable, employee performance. The population consisted of 164 employees, while the sample included 63 respondents selected using purposive sampling. Data were collected through a structured questionnaire distributed via Google Forms and analyzed using SPSS. The analysis included validity and reliability tests, classical assumption tests, multiple linear regression, partial t-test, simultaneous F-test, and coefficient of determination. The results show that rewards do not have a significant effect on employee performance, as indicated by a significance value of 0.904. In contrast, communication has a positive and significant effect on employee performance with a significance value of <0.001, while teamwork also has a positive and significant effect with a significance value of 0.004. Simultaneously, rewards, communication, and teamwork significantly influence employee performance, with an F-value of 77.357 and a significance value of <0.001. The coefficient of determination shows that the three variables explain 79.7% of the variation in employee performance. These findings indicate that employee performance is more strongly supported by effective communication and teamwork than by rewards alone.